2022
DOI: 10.1101/2022.08.25.505296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fan cells in lateral entorhinal cortex directly influence medial entorhinal cortex through synaptic connections in layer 1

Abstract: Standard models for spatial and episodic memory suggest that the lateral entorhinal cortex (LEC) and medial entorhinal cortex (MEC) send parallel independent inputs to the hippocampus, each carrying different types of information. Here, we evaluate the possibility that information is integrated between divisions of the entorhinal cortex prior to reaching the hippocampus. We demonstrate that fan cells in layer 2 (L2) of LEC that receive neocortical inputs, and that project to the hippocampal dentate gyrus, also… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…This is corroborated by our observations that SST + axons are missing from the return pathway connecting LEC to MEC, indicating that, even in the interplay between the entorhinal subregions, the inhibitory connection is exclusively unidirectional from MEC to LEC. Although other inhibitory neuron types could supply LEC-driven inhibition to MEC, it has recently been reported that the LEC–MEC pathway mainly consists of axons from PNiia, which provide excitatory synaptic inputs to principal neurons in superficial layers of MEC (Vandrey et al, 2022). Together, these observations predict that only LEC PNiia, but not their layer II counterparts in MEC, are under direct inhibitory control by the twin entorhinal subdivision and implies that entorhinal interactions are likely to have a contrasting influence on principal neuron activities in layer II of LEC and MEC.…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by our observations that SST + axons are missing from the return pathway connecting LEC to MEC, indicating that, even in the interplay between the entorhinal subregions, the inhibitory connection is exclusively unidirectional from MEC to LEC. Although other inhibitory neuron types could supply LEC-driven inhibition to MEC, it has recently been reported that the LEC–MEC pathway mainly consists of axons from PNiia, which provide excitatory synaptic inputs to principal neurons in superficial layers of MEC (Vandrey et al, 2022). Together, these observations predict that only LEC PNiia, but not their layer II counterparts in MEC, are under direct inhibitory control by the twin entorhinal subdivision and implies that entorhinal interactions are likely to have a contrasting influence on principal neuron activities in layer II of LEC and MEC.…”
Section: Discussionmentioning
confidence: 99%